Protein phosphatase-1 inhibitor-2 promotes PP1γ positive regulation of synaptic transmission - Foley, Karl; Altimimi, Haider; Hou, Hailong; Zhang, Yu; McKee, Cody; Papasergi-Scott, Makaía M.; Yang, Hongtian; Mayer, Abigail; Ward, Nancy; MacLean, David M.; Nairn, Angus C.; Stellwagen, David; et al. (Frontiers in Synaptic Neuroscience, 2022)
Inhibitor-2 (I-2) is a prototypic inhibitor of protein phosphatase-1 (PP1), a major serine-threonine phosphatase that regulates synaptic plasticity and learning and memory. Although I-2 is a potent inhibitor of PP1 in vitro, our previous work has elucidated that, in vivo, I-2 may act as a positive regulator of PP1. Here we show that I-2 and PP1γ, but not PP1α, positively regulate synaptic transmission in hippocampal neurons. Moreover, we demonstrated that I-2 enhances PP1γ interaction with its major synaptic scaffold, neurabin, by Förster resonance energy transfer (FRET)/Fluorescence lifetime imaging microscopy (FLIM) studies, while having a limited effect on PP1 autoinhibitory phosphorylation. Furthermore, our study indicates that the effect of I-2 on PP1 activity in vivo is dictated by I-2 threonine-72 phosphorylation. Our work thus demonstrates a molecular mechanism by which I-2 positively regulates PP1 function in synaptic transmission.